IMPLEMENTATION OF THE “JEMPUT SAMPAH TERIMA DUIT” (JUMPA MADU) WASTE COLLECTION APP TO PROMOTE CLEANLINESS IN LUBUK PAKAM SUBDISTRICT, DELI SERDANG REGENCY - Ronald MS Siburian; Tengku Irmayani; Heri Kusmanto (RADJA PUBLIKA, 2026)
Waste management in Indonesia has become increasingly complex due to population growth, lifestyle changes, and inadequate source-based management. In response, the Deli Serdang Regency government introduced a digital innovation, Jumpa Madu (Jemput Sampah Terima Duit), to enhance waste management efficiency through a technology-based system combined with economic incentives. This study aims to examine the implementation of the Jumpa Madu application in Lubuk Pakam District, focusing on community participation, implementation effectiveness, and the challenges encountered. A descriptive qualitative method with a case study approach was employed. Data were collected through observations, interviews, and documentation involving key stakeholders, including the Environmental Agency, the BERSERI central waste bank, and community users. The findings indicate that community participation is relatively high, particularly among active users who recognize the economic benefits of waste sorting. The application effectively facilitates waste collection scheduling and increases the economic value of segregated waste. However, several challenges persist, including limited digital literacy, constrained technical resources, and uneven access to information. This study concludes that Jumpa Madu represents a promising innovation in strengthening circular economy-based waste management at the local level. Its optimal implementation requires stronger cross-sector collaboration, continuous public education, and improved regulatory and digital infrastructure support.